Early Psychical Research Reference Works: Remarks on Nandor Fodor’s Encyclopaedia of Psychic Science - Alvarado, Carlos S. (Journal of Scientific Exploration, 2020)
Some early reference works about psychic phenomena have included bibliographies, dictionaries, encyclopedias, and general overview books. A particularly useful one, and the focus of the present article, is Nandor Fodor’s Encyclopaedia of Psychic Science (n.d., ca. 1933 or 1934). The encyclopedia has more than 900 alphabetically arranged entries. These cover phenomena such as apparitions, auras, automatic writing, clairvoyance, hauntings, materialization, poltergeists, premonitions, psychometry, and telepathy, but also mediums and psychics, researchers and writers, magazines and journals, organizations, theoretical ideas, and other topics. In addition to the content of this work, and some information about its author, it is argued that the Encyclopaedia is a good reference work for the study of developments before its publication, even though it has some omissions and bibliographical problems. Keywords: Encyclopaedia of Psychic Science; Nandor Fodor; psychical research reference works; history of psychical research